Nutritional Evaluation of Corn Fodder with Hydroponic System with Different Harvest Days as a Substitute for Concentrate Food - Dini Julia Sari Siregar (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
This study aims to find out the effect of harvest time done on corn fodder hydroponic system on the content analysis of ash content, moisture content, coarse protein content, coarse fat content, coarse fiber content, and optimal energy content to be given as animal feed. This study used a Complete Randomized Design (RAL) with 4 treatments and 5 replays where the treatment is P0 = Grass odot harvest age 40 days, P1 = hydroponic corn fodder harvest age 7 days, P2 = corn fodder hydroponic harvest age 9 days, P3 = corn fodder hydroponic harvest age 11 days. The observed parameters are analysis of ash content, moisture content, coarse protein content, coarse fat content, coarse fiber content, and energy content. The results showed that the analysis of the highest ash levels was P0 with an average ash content of 15.36% and differed very noticeablely against P1 with an average low ash content of 7.08%. The highest water content analysis is P3 with an average water content of 87.29% and differs greatly and differs very noticeablely against the P0 with an average water content of 80.86%. The highest rough protein content analysis was P1 with an average rough protein content of 16.04% and differed unreally against P3 with the lowest coarse protein content of 12.63%. The highest rough fat content analysis was P2 with an average rough fat content of 2.33% and differed very noticeablely against P0 with the lowest coarse fat content of 0.44%. The highest rough fiber content analysis was P0 with an average rough fiber content of 22.29% and differed very noticeablely against P0 with the lowest coarse fiber content of 9.82%. The highest energy level analysis is P0 with an average energy content of 3971 kcal and differs very noticeably against P0 with the lowest energy content of 3571 kcal.